Question and Answers Forum

All Questions      Topic List

Relation and Functions Questions

Previous in All Question      Next in All Question      

Previous in Relation and Functions      Next in Relation and Functions      

Question Number 38112 by maxmathsup by imad last updated on 21/Jun/18

prove that  arctan(x)= (i/2)ln(((i+x)/(i−x))) for ∣x∣<1

provethatarctan(x)=i2ln(i+xix)forx∣<1

Commented byprof Abdo imad last updated on 24/Jun/18

we have i+x=x+i=(√(x^2 +1))( (x/(√(x^2  +1))) +(i/(√(x^2  +1))))  =r e^(iθ)  ⇒r=(√(x^2 +1)) and cosθ=(x/(√(x^2  +1)))  sinθ=(1/(√(x^2 +1))) ⇒ tanθ=(1/x) ⇒θ=arctan((1/x)) ⇒  x+i =(√(x^2 +1)) e^(i arctan((1/x)))  ⇒  ln(x+i)=(1/2)ln(x^(2 ) +1) +iarctan((1/x))and  ln(−x+i)=ln(−1) +ln(x−i)  =iπ  +(1/2)ln(x^2 +1)−i arctan((1/x)) ⇒  (i/2)ln(((i+x)/(i−x)))=(i/2){ln(i+x)−ln(i−x)}  =(i/2){ 2i arctan((1/x))−iπ}  =(π/2) −arctan((1/x))=arctan(x) if 0<x<1  if −1<x<0 we use the chang.x=−t...

wehavei+x=x+i=x2+1(xx2+1+ix2+1) =reiθr=x2+1andcosθ=xx2+1 sinθ=1x2+1tanθ=1xθ=arctan(1x) x+i=x2+1eiarctan(1x) ln(x+i)=12ln(x2+1)+iarctan(1x)and ln(x+i)=ln(1)+ln(xi) =iπ+12ln(x2+1)iarctan(1x) i2ln(i+xix)=i2{ln(i+x)ln(ix)} =i2{2iarctan(1x)iπ} =π2arctan(1x)=arctan(x)if0<x<1 if1<x<0weusethechang.x=t...

Answered by tanmay.chaudhury50@gmail.com last updated on 22/Jun/18

ln(α+iβ)=(1/2)ln(α^2 +β^2 )+i(2nΠ+tan^(−1) (β/α))  ln(((i+x)/(i−x)))=ln(i+x)−ln(i−x)  ln(i+x)=(1/2)ln(1+x^2 )+i(2nΠ+tan^(−1) (1/x))  ln(i−x)=(1/2)ln(1+x^2 )+i(2nΠ+tan^(−1) (1/(−x)))  ln(((i+x)/(i−x)))=i(tan^(−1) (1/x)−tan^(−1) (1/(−x)))  =i(2tan^(−1) (1/x))  so the value  (i/2)ln(((i+x)/(i−x)))  (i/2)×i(2tan^(−1) (1/x))  =−tan^(−1) ((1/x))=tan^(−1) (x)−(Π/2)  since  tan^(−1) x=k  tank=x  cotk=(1/x)  tan((Π/2)−k)=(1/x)  tan^(−1) ((1/x))=(Π/2)−k  tan^(−1) ((1/x))+tan^(−1) (x)=(Π/2)

ln(α+iβ)=12ln(α2+β2)+i(2nΠ+tan1βα) ln(i+xix)=ln(i+x)ln(ix) ln(i+x)=12ln(1+x2)+i(2nΠ+tan11x) ln(ix)=12ln(1+x2)+i(2nΠ+tan11x) ln(i+xix)=i(tan11xtan11x) =i(2tan11x) sothevalue i2ln(i+xix) i2×i(2tan11x) =tan1(1x)=tan1(x)Π2 since tan1x=k tank=x cotk=1x tan(Π2k)=1x tan1(1x)=Π2k tan1(1x)+tan1(x)=Π2

Terms of Service

Privacy Policy

Contact: info@tinkutara.com